IN SITU TIME RESOLVED SYNCHROTRON POWDER DIFFRACTION STUDY OF THAUMASITE - Martucci A.; Cruciani G. (My University, 2006)
Structural changes during dehydration and subsequent decomposition in thaumasite Ca3Si(SO4)(CO3)(OH)6·12 H2O were studied by in situ synchrotron powder diffraction between 303 and 1,098 K. Evolution of the crystal structure was observed through 28 structure refinements, by full profile Rietveld analysis performed in the P63 space group, between 300 and 417 K, whereupon the thaumasite structure was observed to breakdown. Within this temperature range, the cell parameters of thaumasite increased as a function of temperature in a nearly linear fashion up to about 393 K, at which temperature, a slight slope change was observed. Above 400 K, the thermogravimetric analysis revealed that the dehydration process proceeded very rapidly while the refined occupancy of water molecules dropped below a critical level, leading to instability in the thaumasite structure. At a same time, a remarkable change in the unit cell parameters occurring at about 417 K indicated that the crystal structure of thaumasite collapsed on losing the crystallization water and it turned amorphous. This result indicated that the dehydration/decomposition of thaumasite was induced by the departure of the crystallization water. At about 950 K, anhydrite and cristobalite crystallized from the thaumasite glass.
Keywords: THAUMASITE; HEATING PROCESS; IN SITU POWDER DIFFRACTION; X-RAY SYNCHROTRON RADIATION; RIETVELD ANALYSIS